Dynamic cytokinin signalling landscapes during lateral root formation in Arabidopsis - Nenadić, Milica; Vermeer, Joop (My University, 2021)
By forming lateral roots, plants expand their root systems to improve anchorage and absorb more water and nutrients from the soil. Each phase of this developmental process in Arabidopsis is tightly regulated by dynamic and continuous signalling of the phytohormones cytokinin and auxin. While the roles of auxin in lateral root organogenesis and spatial accommodation by overlying cell layers have been well studied, insights on the importance of cytokinin is still somewhat limited. Cytokinin is a negative regulator of lateral root formation with versatile modes of action being activated at different root developmental zones. Here, we review the latest progress made towards our understanding of these spatially separated mechanisms of cytokinin-mediated signalling that shape lateral root initiation, outgrowth and emergence and highlight some of the enticing open questions.
Keywords: Arabidopsis; cytokinin; cytokinin transport; lateral roots.